2006
DOI: 10.1300/j081v20n01_07
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Intention to Quit Among Frontline Assisted Living Employees

Abstract: Assisted livings face high rates of employee turnover; and nursing homes with high employee turnover report reduced quality of care for residents, lower employee morale, and financial burden for the facility owners. Five communities in Georgia were examined to determine the affects of employee turnover. The Job Descriptive Index and Job-in-General surveys measured job satisfaction. Thirty-six respondents' attitudes and intention to quit were measured. Results indicated age and tenure did not correlate signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…From the 44 quality assessments, 5 (11%) studies were rated strong [ 9 , 78 , 81 , 84 , 85 ], 6 (14%) high moderate [ 53 , 56 , 66 68 , 73 ], 15 (34%) low moderate [ 10 , 52 , 57 , 58 , 61 , 64 , 65 , 69 , 71 , 72 , 75 , 76 , 78 , 83 , 93 ], and 18 (41%) weak [ 33 , 46 – 49 , 51 , 54 , 55 , 59 , 60 , 62 , 70 , 74 , 77 , 79 , 80 , 82 ]. Differences in quality assessment arose mainly from sample representativeness, treatment of missing data, and appropriateness of statistical test(s) used.…”
Section: Resultsmentioning
confidence: 99%
“…From the 44 quality assessments, 5 (11%) studies were rated strong [ 9 , 78 , 81 , 84 , 85 ], 6 (14%) high moderate [ 53 , 56 , 66 68 , 73 ], 15 (34%) low moderate [ 10 , 52 , 57 , 58 , 61 , 64 , 65 , 69 , 71 , 72 , 75 , 76 , 78 , 83 , 93 ], and 18 (41%) weak [ 33 , 46 – 49 , 51 , 54 , 55 , 59 , 60 , 62 , 70 , 74 , 77 , 79 , 80 , 82 ]. Differences in quality assessment arose mainly from sample representativeness, treatment of missing data, and appropriateness of statistical test(s) used.…”
Section: Resultsmentioning
confidence: 99%
“…Burnout is a critical factor that affects educator's intent to leave the profession (Kusy & O'Leary-Driscoll, 2020). The causal model of turnover (Mobley, 1977) has provided the theoretical framework for many studies on turnover and asserts that dissatisfaction at work may lead to thoughts and intentions of quitting, which is the direct precursor of actual voluntary turnover (Jeswani & Dave, 2012;Purk & Lindsay, 2006). This study sought to understand how the work environment and burnout influence the extent to which an employee plans to separate from their place of employment.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Furthermore, intent to stay was linked to resident satisfaction with relationships to staff and their reports of quality of life (Bishop et al, 2008). Purk and Lindsay (2006) studied the relationship of job satisfaction, as well as personal characteristics and attitudes, with intent to quit. They found that workers who experienced dissatisfaction with elements of their job were more likely to report their intent to quit.…”
Section: Job Satisfactionmentioning
confidence: 99%